Agrarian Reform In The Perspective of Pancasila - Mas Subagyo Eko Prasetyo (LEGAL BRIEF, 2020)
In the construction of the thought of the Preamble to the 1945 Constitution, Pancasila is the basis of the state which is the subject of the fundamental rules of the state and is the highest norm in the hierarchy of the system of legal norms of the Republic of Indonesia. Pancasila is the basic norm that creates all lower norms in the legal system. Pancasila should also determine whether or not the legal norms under it apply. In the thought construction of the Preamble to the 1945 Constitution, Pancasila will be realized through the making and implementation of state policies (the constitution, laws, government regulations and so on to the lowest implementing regulations) and is revealed in the practices and habits of acting of the administrators of state power, executive, legislative and judicial. Law number 5 of 1960 concerning the Basic Agrarian Regulations, better known as the Basic Agrarian Law (UUPA) can be put forward as an example of Indonesia's positive law which flows directly from Pancasila (especially the principles of Social Justice) and Law No. The 1945 Constitution (especially Article 33 paragraph 3), although in practice the law seems to have been deliberately not implemented because of the complexity of the interests that played out after the open door policy was implemented in 1967.